Effect of water absorption on graphene nanoplatelet and multiwalled carbon nanotubes-impregnated glass fibre-reinforced epoxy composites - Ahmad, M. A. A.; Ridzuan, M. J. M.; Abdul Majid, M. S.; Sapuan, S. M.; Shahriman, A. B; Mat, Fauziah (Springer Science and Business Media, 2023)
In this study, the effect of water uptake on graphene nanoplatelets (GNP) and multiwalled carbon nanotube (MWCNT)-impregnated glass fibre-reinforced epoxy composites was examined. The composite was manufactured using a hand lay-up and vacuum bagging technique. The nanofiller was mixed with epoxy using a mechanical stirrer, high-shear mixer, and ultrasonic probe machine. In situ electromechanical testing was performed on the specimens. The study found that the weight content and type of nanofiller impact the composites' water uptake and mechanical properties. The water uptake of GNP–glass, MWCNT–glass, and GNP–MWCNT–glass hybrid composites decrease with the addition of different nanofiller contents. Adding a 1.5 GNP–MWCNT hybrid mixture increased the composite's tensile and flexural strengths to 269.3 and 294.4 MPa, respectively. The GNP–MWCNT–glass hybrid composite shows a positive synergy effect on the enhancement of water-ageing with self-sensing ability, while the GNP–glass, MWCNT–glass composites show a less positive effect on water ageing sensing behaviour. The nanofillers dispersion and fracture surface morphological observations were disclosed using a field emission scanning electron microscope. The results established that the GNP–MWCNT–glass hybrid exhibits good potential for in situ damage monitoring of composites and can support their development and application as a smart material.